2018
DOI: 10.1016/j.isci.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Mutagenesis Screen of the Adhesion GPCR Latrophilin-1/ADGRL1

Abstract: SummaryAdhesion G-protein-coupled receptors (aGPCRs) play critical roles in diverse cellular processes in neurobiology, development, immunity, and numerous diseases. The lack of molecular understanding of their activation mechanisms, especially with regard to the transmembrane domains, hampers further studies to facilitate aGPCR-targeted drug development. Latrophilin-1/ADGRL1 is a model aGPCR that regulates synapse formation and embryogenesis, and its mutations are associated with cancer and attention-deficit/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 70 publications
6
75
0
Order By: Relevance
“…The extracellular domains of ADGRLs have been demonstrated to associate with a remarkable diversity of synaptic adhesion molecules both in cis and in trans, as accounted below. Although ADGRLs are generally known for their contributions to extracellular structure, recent studies have conclusively demonstrated their ability to couple to canonical G protein pathways and thus serve as bona fide GPCRs (Li et al, 2018;Nazarko et al, 2018). Mechanistically, the multitude of extracellular and transcellular interactions of ADGRLs are capable of stabilizing various states of receptor activation/inactivation to coordinate cellular processes from neurite outgrowth, axonal attraction, and synaptogenesis to axonal repulsion and apoptosis.…”
Section: Multimodal Assemblies Involving Adhesion Gmentioning
confidence: 99%
“…The extracellular domains of ADGRLs have been demonstrated to associate with a remarkable diversity of synaptic adhesion molecules both in cis and in trans, as accounted below. Although ADGRLs are generally known for their contributions to extracellular structure, recent studies have conclusively demonstrated their ability to couple to canonical G protein pathways and thus serve as bona fide GPCRs (Li et al, 2018;Nazarko et al, 2018). Mechanistically, the multitude of extracellular and transcellular interactions of ADGRLs are capable of stabilizing various states of receptor activation/inactivation to coordinate cellular processes from neurite outgrowth, axonal attraction, and synaptogenesis to axonal repulsion and apoptosis.…”
Section: Multimodal Assemblies Involving Adhesion Gmentioning
confidence: 99%
“…Indeed, when LTX N4C acts via the NTF–CTF complex, it clearly stimulates Gαq‐mediated signaling via PLC to internal Ca 2+ stores . On the other hand, the CTF of LPHN1 expressed without the NTF demonstrates a different signaling specificity and (at least when it is stimulated by exogenous Stachel peptide) activates Gαi, leading to a decrease in cAMP levels . Thus, the activation of one signaling pathway may cause the CTF to dissociate from the complex and switch to another signaling pathway, where the CTF could act as a nonadhesion GPCR.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies on the signaling mechanisms of aGPCRs have largely been aided by the development of signaling assays which can probe the functions of specific receptors. Previous works on ADGRL1 (latrophilin‐1) using newly established signaling assays have allowed a better understanding of how aGPCRs function and to probe the signaling effects of cancer mutations . Leon and colleagues found that ADGRL1 is activated by its Stachel peptide, similar to other aGPCRs, and studied the residues important for Stachel ‐mediated activation.…”
Section: Introductionmentioning
confidence: 99%
“…aGPCRs have large extracellular regions (ECRs) decorated by numerous adhesion domains and a conserved GPCR autoproteolysis inducing (GAIN) domain that mediates self‐cleavage of the receptor. Two avenues of research from her group were discussed: Araç and colleagues showed that aGPCRs are activated via Stachel ‐independent mechanisms in addition to Stachel ‐dependent mechanisms . Stachel ‐independent mechanisms depend on the large ECRs of aGPCRs and form the basis for the complex regulation of aGPCR function. They also determined the high‐resolution structure of teneurin, a large ligand of ADGRL1 (latrophilin/LPHN1) and revealed a unique structure that is similar to bacterial Tc toxins .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation